Topical Retinoid In Treatment of Molluscum Contagiosum in Iraqi patients in Khalis City (Placebo Control Study) - Mahdi, Mohammed Ahmed; Mukheilf, Tahseen Abdulzahera (Diyala Journal of Medicine, 2018)
Background: Molluscum Contagiosum is a common cutaneous viral infection seen in children and adults. It is caused by a DNA virus, related to Pox group of viruses. Objective: To determine the efficacy of topical retinoids in treatment of Molluscum Contagiosum patients in Khalis City. Patients and Methods: A placebo control study was carried out during the period from 1st December 2015 till 1st August 2016; forty patients with Molluscum Contagiosum in Khlalis City (24 males and 16 females, with age group range between 3-40 years) were randomly divided into two groups. The group 1 has given 0.05% topical retinoids cream to be applied at bed time over lesions. The group 2 has given placebo (aquarosa) to be applied at the bed time over the lesions; the durations of treatment were six weeks for both groups. Results: At the end of six weeks the first group shows 65% healing rate (13 patients) with mean lesions number decrease from 9 to 2; while the second’s group only one patient shows complete healing (5%) with mean lesions number decrease from 9 to 7. Conclusion: Topical retinoid is effective treatment of Molluscum Contagiosum after Six weeks course of treatment as compared with placebo with success rate of 65% and 5% respectively.